PENERAPAN DATA MINING MENGGUNAKAN ALGORITMA K-MEANS UNTUK MENGETAHUI MINAT CUSTOMER DI TOKO HIJAB - Yulianti, Yulianti; Utami, Dwi Yuni; Hikmah, Noer; Hasan, Fuad Nur (LPPM Universitas Nusa Mandiri, 2019)
Hijab is not a foreign thing for the population in Indonesia, because most of the population of Indonesia is Muslim. Today, many business people, especially hijab sellers, provide a variety of brands and models in the hijab they sell. Therefore sellers are required to be able to think intelligently in making a sales strategy that will certainly be useful to know clearly which products are most in demand by customers, and also to increase sales in their stores. Then there needs to be an alternative that can realize the recording of sales transaction data more quickly and structured. In this study the authors applied the k-means algorithm to determine customer interest in the products they sell. In the calculation that has been done by using two parameters, namely the transaction and the number of sales and passing three iterations with the results of iterations one gets a ratio of 0.374324132, the iteration two gets the ratio 0.543018325, and the iteration three gets the same ratio value as second iteration. So it can be concluded that the hijab that is most desirable by the customers is the hijab with the brand Rabbani, Elzatta, and Zoya, the low-interest hijab branded by Dian Pelangi, Kami Idea, and Meccanism. And the hijab with those who are not high and also not low is the hijab under the brand Ria Miranda, Jenahara, Shasmira, and Shafira.